Implementing the Dick and Carey Model in Al-Qur'an Instruction within Out-of-School Majelis Taklim Settings - Ima Maisaroh; Nanah Sujanah; Sholeh Hidayat; Luluk Asmawati; Naniek Afrilla Framanik; Nina Yuliana (International Journal of Nusantara Islam, 2026)
Majelis Taklim is a non-formal educational institution that plays a crucial and strategic role in enhancing the community's Qur'an literacy, but is often hindered by the heterogeneity of participants, limited resources, and the lack of a systematic teaching framework. The Dick & Carey model, with its systematic instructional design approach, offers a solution for designing structured and effective Qur'anic learning. This study aims to analyze the application of the Dick & Carey model in learning the Qur'an in Majelis Taklim, identify supporting factors and obstacles, and develop innovative recommendations to optimize the learning process in the digital era. This research uses a qualitative approach with a literature study design collected from various sources such as SINTA indexed journals, books, and official documents through systematic searches on Google Scholar, Publish or Perish and so on. Data analysis was conducted through content analysis techniques, including data reduction, data presentation based on themes, and conclusion drawing, with source triangulation to ensure validity. This research is theoretically useful in enriching the discourse on non-formal religious learning design and provides practical guidance for managers and educators (asatidh) in Majelis Taklim on designing learning integrated with technology. This research concluded that the Dick & Carey Model has proven to be effective with its systematic stages, especially, reinforced by technology such as the Al-Qur'an application and social media. However, it is necessary to first increase knowledge and skills in instructional design, utilize digital platforms, and conduct empirical tests through training the educators.